Osteoporosis and vertebral trabecular bone health: an historico-anthropological perspective - Galassi, Francesco M.; Varotto, Elena (Anthropological Review, 2023)
This brief review article aims to recapitulate the history of osteoporosis from the most ancient observations to the current clinical definition, by offering a perspective on trabecular bone health and degeneration, which has become of paramount important both in clinical, radiological and biological anthropological studies.